Digital Lighting & Rendering - Birn, Jeremy (Indianapolis New Riders, 2003)
Digital Lighting contains strategies for lighting design that are relevant to any digital artist. It presents an awareness of computer lighting models, how they differ from real-world lighting effects, and how to approach 3D lighting projects differently from practical light. Topics covered include: What good lighting can do for you; Light sources; Shading; Shadows; Exposure and content; Color: temperature, correction, mood; Qualities of light; 3-point lighting; Indirect illumination; Multipass rendering and compositing; Lighting in production; and Case studies: natural lighting, interior lighting, character lighting, and effects lighting.
Includes Colored Illustrations and Index.
Keywords: Computer graphics